Pembinaan Produksi Kompos Limbah Pertanian dan Pemanfaatannya di Kecamatan Tamansari, Kabupaten Bogor - Asdar Iswati; Lilik Tri Indriyati (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
Most of agricultural lands in Pasir Eurih Village are paddy field simple irrigation system, while most of them in Sukajadi Village are upland. Farmers in both villages are used to composting organic residues, but the composts was not used maximally. The aim of the IbM activities was: (1) To guide our partners to produce better quality of composts sustainable; and(2) To motivate the community of peasant  using composts for their farm. The best compost resulted by IbM-3 guidance was made from rice straw, leaf litter, and chicken manure mixed with rice husk as their bedding by ratio of 3:2:1:1. This compost contained macronutrients (N, 0.56%, P2O5  1.09%, K2O 1.44%, Ca 5.72%, Mg 0.43%, and Na 0.08% respectively), micronutrients Fe 5.309 ppm, Mn 342 ppm, Cu 42 ppm, Zn 69 ppm, and B 33 ppm respectively), and heavy metals of Pb was 4.8 ppm and Cd 0.04 ppm. The addition of 3-4 ton/ha of this compost into paddy soil could reduce chemical fertilizers up to 50%. The addition of 3 ton/ha of this compost to upland soil planted by sweet corn produce same with application of chicken manure bedding or goat manure. Socialization of the benefit of using compost in increasing the soil fertility and crop yield have raised the peasant’s knowledge. It was showed by the mean value of this post test raised 19.67 points for fertilizer and soil fertility matter and 16.63 points for organic materials or natural fertilizers matter.